High socioeconomic impact on prescription behavior despite unrestricted access to disease-modifying therapies in people with multiple sclerosis - Samadzadeh, S.; Havla, J.; Lepka, K.; Brinks, R.; Meuth, S. G.; Klotz, L.; Albrecht, P. (Frontiers in Immunology, 2024)
Background: Economic and health care restraints strongly impact on drug prescription for chronic diseases. We aimed to identify potential factors for prescription behavior in chronic disease. Multiple sclerosis was chosen as a model disease due to its chronic character, incidence, and high socioeconomic impact. Methods: Germany was used as a model country as the health-care system is devoid of economic and drug availability restraints. German statutory health insurance data were analyzed retrospectively. The impact of number of university hospitals and neurologists as well as the gross domestic product (GDP) as potential factors on prescriptions of platform and high-efficacy disease-modifying therapies (DMTs) was analyzed.Results: Prescription of platform DMTs increased over time in almost all federal states with varying degree of increase. Univariate regression analysis showed that the prescription volume of platform DMTs positively correlated with the number of university hospitals and neurologists, as well as the GDP per federal state. Stepwise forward regression analysis including all potential factors indicated a statistically significant model for platform DMT (R 2 =0.55; 95%-CI [0.28, 0.82]; p=0.001) revealing GDP as the main contributor. This was confirmed in the independent analysis.This study illustrates that even without overt drug prescription inequity, access to medication is not evenly distributed and depends on economic strength and regional medical care density.